SAT0071 Early Initiated Etanercept Plus Methotrexate Treatment Induces Remission in Patients with Either Moderate or Severe Rheumatoid Arthritis. (23rd January 2014) - Emery, P.; Szumski, A.; Bukowski, J.; Bananis, E.; Marshall, L.
Abstract : Background: Early aggressive treatment of RA has been shown to improve clinical outcomes but identifying patients (pts) who may benefit is challenging. The majority of findings from treatment trials have been derived from pts with severe RA; less is known about the larger group of pts with moderately active disease who may benefit from early effective therapy. During the first period of the PRIZE study, designed to evaluate combined etanercept plus methotrexate (ETN/MTX) efficacy in pts with early, active moderate-to-severe RA, DAS28 LDA (≤3.2) was achieved in >75% of pts and DAS28 and SDAI remission in >60% of pts. Objectives: To compare baseline characteristics and treatment outcomes of moderate vs severe RA pts with early disease over 39 wks in Period 1 of the PRIZE study. Methods: In Period 1 of PRIZE (52‑wk open-label, single-arm portion) all early MTX-naïve RA pts received ETN 50 mg QW + MTX. Pts with DAS28 >3.2 received corticosteroid boosts at wks 13 and/or 26; those not achieving LDA at wk 39 were withdrawn. Standard clinical outcomes were assessed in pts with moderate (DAS28 >3.2─≤5.1) or severe disease (DAS28 >5.1) at baseline. Analyses using OC were conducted in all pts who received ≥1 ETN/MTX dose (mITT). Results: Of 306 pts who received treatment in Period 1, 63 (20.6%) had moderate and 242 (79.1%) had severe disease at baseline. Baseline values were as expected, with severe pts having significantly greater disease activity in all parameters assessed. Efficacy assessments of pts that completed 39 wks of treatment are summarized in the Table . Significant changes from baseline to wk 39 were observed for all clinical endpoints in both moderate and severe RA groups (all P<0.0001) with significant between-group differences for DAS28 and CDAI (P<0.05). ACR Boolean remission was achieved in 35/57 pts (61.4%) with moderate disease and 101/201 (50.2%) of those with severe disease (P=0.18); corresponding values for SDAI remission were 68.4% (39/57) and 54.0% (107/198) (P=0.068). While there were no significant differences between moderate and severe groups at 39 wks, a greater proportion of moderate than severe pts achieved remission at earlier timepoints (SDAI remission: 41% vs 21% (P<0.01) at wk 13; 55% vs 40% (P=0.04) at wk 26). Conclusions: Of early RA pts completing 39 wks of treatment, most achieved remission with 50 mg ETN/MTX regardless of baseline disease severity. A higher proportion of moderate than severe pts achieved remission earlier in the treatment time course, although remission rates between moderate and severe groups were no longer significantly different after 39 wks. Pts with severe activity require a larger DAS improvement to reach LDA and remission and may need a longer period to achieve these outcomes. Acknowledgements: The PRIZE study was funded by Pfizer Inc. Disclosure of Interest: P. Emery Consultant for: Abbott, Bristol-Myers Squibb, Merck, Novartis, Pfizer Inc, Roche-Chugai, UCB Pharma Ltd, A. Szumski Employee of: Pfizer Inc, J. Bukowski Employee of: Pfizer Inc, E. Bananis Employee of: Pfizer Inc, L. Marshall Employee of: Pfizer Inc